Suprapubic Catheterization in Neurogenic Bladder by Distending Bladder with Air-A Novel Technique - Sun, Xinghui (International Journal of Innovative Research in Medical Science, 2021)
Suprapubic catheterization (SPC) in patients with neurogenic bladder (NGB) is difficult and high risk. Our aim is to provide a novel SPC method in patients with NGB by distending the bladder with air. A total of 26 patients with NGB underwent SPC using this new method. The bladder was first filled with air based on its volume of urine or liquids. Then, a reusable trocar was advanced into the bladder as per the general method. Preoperative demographics of patients and operative details were recorded. SPC was performed under local anaesthesia in 26 patients with NGB, including 18 men and 8 women. The mean age of the patients was 36 years (range, 28-77). An 18F Foley catheter was used for all patients. Blood loss was minimal, and the procedure was performed successfully in all patients without any complication. By distending the bladder with air, the SPC method is presented as an effective and safe method suited for patients with NGB. To our knowledge, this is the first report of this novel procedure.